Features of experimental modeling of tuberculosis in guinea pig with the participation of N '-(2-(5-((thephylline-7 '-yl)methyl)-4-R-1,2,4-triazole-3-ylthio)acethyl)isonicotinohydrazide - Gotsulya, А. S.; Zazhzharskiy, V. V.; Davidenko, P. O.; Zazhzharskaya, N. M.; Kulishenko, O. M.; Panasenko, O. I.; Gutyj, B. V.; Pryima, O. B.; Mazur, I. Y.; Pritsak, V. V.; Drachuk, U. R.; Sobolta, A. G.; et al. (My University, 2020)
In this study, no toxic effects were detected after single subcutaneous injection of 40 mg/kg tadpoles. The results of macro- and microscopic examination of the internal organs 14 days after single subcutaneous administration of N'-(2-(5-((thephylline-7'- yl)methyl)-4-ethyl-1,2,4-triazole-3-ylthio)acethyl)isonicotino-hydrazide (GKP-305) at a dose of 20, 40 mg/kg showed the absence of any anatomical and morphological abnormalities in the tissue structures of the tentacles. The calculated value of the drug indicates a high degree of safety GKP-305 and its prospects for veterinary practice as an effective and safe tuberculocidal drug.
Keywords: tuberculosis; 1,2,4-triazole; modeling; guinea pig